Rice cultivation system with less water consumption for sustainable future - Fazli, Pardis; Che Man, Hasfalina; Mohamed Zawawi, Mohamed Azwan; Md. Shah, Umi Kalsom; Abdul Rahman, Nor'aini; Idris, Azni; Mohd Yusof, Mohd Rashid (2015)
Rice is a main food for about one third of the world’s population. Besides, the demand for this crop is anticipated to rise with growing population of the world. Increasing the rice cultivation area can be a fulfillment to hit adequate rice production. Rice crop is mostly produced by conventional method with flooding the soil. Consequently, a remarkable amount of water is used for rice production. This fact emphasizes the necessity of finding a water-saving cultivation system concerning a sustainable future. Current two-round research studied different irrigation systems for rice under different cultivation methods including, original system of rice intensification (SRI), oblong-triangular system of rice intensification and conventional method in relation to water savings. Consequently, more than 40% water saving was observed in SRIs while higher water productivity recorded in these cultivation systems (> 7 kg ha-1 mm-1) compared to conventional method (> 4 kg ha-1 mm-1).